2002
DOI: 10.1002/cncr.10916
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase 1, matrix metalloproteinase 2, and matrix metalloproteinase 9 in carcinoma of the head and neck

Abstract: BACKGROUNDNumerous reports have documented a direct involvement of matrix metalloproteinase (MMP) overexpression in the development and progression of head and neck squamous cell carcinoma (HNSCC). In this study, the authors examined whether the expression of MMPs in HNSCC is correlated with other steps involved in tumor growth and metastasis, like angiogenesis, activation the nitric oxide (NO) pathway, and alteration of the p53 tumor suppressor gene.METHODSMMP‐1, MMP‐2, and MMP‐9 expression levels were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
120
2
8

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 45 publications
14
120
2
8
Order By: Relevance
“…Due to lack of data, however, nine articles had to be excluded from the current metaanalysis. The remaining 5 publications with a total of 238 patients 7,9,[17][18][19] demonstrated MMP-9 expression in 150 tissue specimens. The common odds ratio is summarized in Table 2.…”
Section: Results For Mmp-9mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to lack of data, however, nine articles had to be excluded from the current metaanalysis. The remaining 5 publications with a total of 238 patients 7,9,[17][18][19] demonstrated MMP-9 expression in 150 tissue specimens. The common odds ratio is summarized in Table 2.…”
Section: Results For Mmp-9mentioning
confidence: 99%
“…cN status and pN status were considered in two publications, 7,17 whereas one publication considered only pN status, 18 and two other publications 9,19 did not provide any information about lymph node status. None of the studies mentioned compared levels of MMP-expression with cN status or pN status.…”
Section: Results For Mmp-9mentioning
confidence: 99%
“…26 These data indicate that poorly differentiated oral cancer in Taiwan is significantly lower than the report of 21-42.8% in the Western countries. 8,27 It is unknown if different location of the oral cancer, the different etiology or different races may account for the observed difference in the percentage of cell types. MMP-7, also known as matrilysin-1, is the smallest member of the MMP family, 15,28 as it lacks the C-terminal hemopexin domain common to other MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of MMPs in head and neck cancers has been reported. [4][5][6][7][8][9][10][11][12][13][14] Those studies demonstrated that immunoreactive MMP-2 and MMP-9 staining was stronger in patients with lymph node metastasis and was associated with lower survival rates. [11][12][13][14] MMP-7 is one of the few MMPs overexpressed by carcinoma cells rather than by stromal cells.…”
mentioning
confidence: 99%
“…5 Overexpression of MMP1 has been demonstrated in HNSCC tissues and has been found to be associated with poor outcome. 3,[6][7][8] The expression of MMP1 is partly regulated by its upstream promoter sequences. 9 Recently, a functional single nucleotide polymorphism (SNP) in the promoter region of the human MMP1 has been reported.…”
mentioning
confidence: 99%